Information Technology and International Competitiveness : The Case of the Construction Services Industry - United Nations Conference on Trade and Development (New York : United Nations, 1993)
This book is intended to improve understanding of the interrelationship between information technology and international competitiveness in construction services. It gives a detailed analysis of the international dimension of the industry and reviews the experience of selected construction and engineering services firms from a few developed countries, namely the United States, the United Kingdom and Sweden, where the diffusion of information technology has increased at different rates since the second half of the 1980s.
At head of title: United Nations Conference on Trade and Development.
"UNCTAD/ITD/TEC/6."
"United Nations publication sales no. E.93.II.D.6"--T.p. verso.
Includes bibliographical references.
ne 12/04/2018
Loans
Keywords: Information Technology Infrastructure; Construction Industry